2010
DOI: 10.1007/s00894-010-0775-8
|View full text |Cite
|
Sign up to set email alerts
|

Computational design of a lipase for catalysis of the Diels-Alder reaction

Abstract: Combined molecular docking, molecular dynamics (MD) and density functional theory (DFT) studies have been employed to study catalysis of the Diels-Alder reaction by a modified lipase. Six variants of the versatile enzyme {\em Candida Antarctica} lipase B (CALB) have been rationally engineered {\em in silico} based on the specific characteristics of the pericyclic addition. A kinetic analysis reveals that hydrogen bond stabilization of the transition state and substrate binding are key components of the catalyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 84 publications
2
24
0
Order By: Relevance
“…As seen from the corresponding columns in Table 3, the 'absolute' TS stabilization is small and amounts to at most À2.2 kcal/mol (1c+2). This result correlates with previous findings by ourselves 19,20 and others, 15,16 stating that the stabilization of the TS is a relatively small portion of the net catalytic effect. The fact that ΔG NAC ‡ for 1d is larger than the corresponding uncatalyzed energy is a consequence of interactions in the active site that hinders the TS formation.…”
Section: Journal Of Chemical Information and Modelingsupporting
confidence: 94%
See 1 more Smart Citation
“…As seen from the corresponding columns in Table 3, the 'absolute' TS stabilization is small and amounts to at most À2.2 kcal/mol (1c+2). This result correlates with previous findings by ourselves 19,20 and others, 15,16 stating that the stabilization of the TS is a relatively small portion of the net catalytic effect. The fact that ΔG NAC ‡ for 1d is larger than the corresponding uncatalyzed energy is a consequence of interactions in the active site that hinders the TS formation.…”
Section: Journal Of Chemical Information and Modelingsupporting
confidence: 94%
“…We have been able to reach a high degree of shape complementarity, leading to extremely high formation of 'near-attack conformers' compared to previous designs. 9,19 Understanding and designing enzyme catalysis is a complex problem which requires a range of methods, and with this work, we have shown that a combination of several standard, well-established techniques gives detailed information and control of the design process. We have improved the chance of success by not designing to a specific pair of reagents, instead selecting reagent pairs most likely to be optimum for a given set of mutations.…”
Section: ' Conclusion and Outlookmentioning
confidence: 99%
“…The predicted functional covariant residues are shown in Figure A whose function includes the activity, thermostability, and enantioselectivity. And the residues in red are reported functional sites . For example, E188 has a strong correlation with W104, D134, and M129 (Figure B).…”
Section: Resultsmentioning
confidence: 99%
“…We have been interested in re-designing enzymes containing an 'oxyanion hole’ moiety[68] to catalyze the intermolecular Diels-Alder reaction, which is virtually unknown in nature[6971] and therefore highly interesting for de novo design. [2] Our work was initially guided by a rational design framework (Figure 1a),[72] which can be said to rely on the concept of 'catalytic promiscuity’. [73] Catalytic promiscuity is in turn a manifest of evolutionary heritage,[23, 74, 75] where a wide array of reactions can be catalyzed by structurally and functionally similar enzymes.…”
Section: Searching For Matching Functionalitiesmentioning
confidence: 99%
“…Another key feature of our approach is that we rely on molecular dynamics (MD) simulations for evaluation, selection and quantification of different variants,[72, 76] a practice that has recently begun appearing in several other studies (Figure 1b). [21, 67, 79] We refer to this as ‘dynamic design’.…”
Section: Including Dynamicsmentioning
confidence: 99%